Implementasi Peran Lembaga Perlindungan Perempuan dan Anak dalam Memberikan Bantuan Hukum terhadap Korban KDRT di Kabupaten Lampung Utara - Wulan Atma Putri; Slamet Haryadi (Himpunan Ilmu Hukum dan Ilmu Hukum Islam, 2025)
Domestic violence (DV) remains a serious issue affecting women and children in North Lampung Regency, requiring an effective role from LPPA/DPPPA in providing protection and legal assistance. This study uses an empirical juridical method through statutory, sociological, and case approaches. The results show that LPPA/DPPPA conducts initial assessments, supports victims during police reporting, coordinates with law enforcement and service institutions, and accompanies victims throughout court proceedings, including non-litigation services such as counseling and health referrals. Obstacles include limited human resources, inadequate facilities, and low public awareness. Strengthening capacity, cross-sector coordination, and public education is needed to enhance victims’ access to justice.